The effect of neural mobilization of the brachial plexus on the flexibility of the lower limb: a double-blind trial. - Valente, Priscila de Souza; Valente, Priscilane de Souza; Silva, Augusta da; Arêas, Guilherme Peixoto Tinoco; Júnior, Renato Campos Freire; Maciel, Thiago dos Santos; Arêas, Fernando Zanela da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The technique of neural mobilization promotes ease in carrying out the movement and they elasticity of the nervous system, creating and perfecting straining their normal functions, with resulting increase in range of motion . Objective: The aim of this study was to evaluate the effects of neural mobilization of the brachial plexus on the gain range of motion in the lower limbs in asymptomatic individuals. Method: The evaluation was conducted in three steps , immediate post-neural pre-mobilization and post - late , by testing the 3rd finger to the ground test and fleximetry. The technique of brachial plexus neural mobilization was applied for ten days, with three weekly sessions to complete ten days (four weeks), performed on alternate days, with a minimum interval of 24 hours between sessions. The sample consisted of 17 sedentary college students, between 18 and30 years, . All statistical analysis was performed with (p<0.05). Results: In assessing the hamstrings and quadriceps with fleximeter there was not a statistically significant gain range of motion after neural mobilization , however, there was a significant increase in overall flexibility evaluated with the test of the 3rd finger soil to reach the left finger. Conclusion: In this study, neural mobilization brachial plexus got no efficacy to gain range of motion of the lower limbs in asymptomatic individuals. However, the overall results showed earned flexibility to reach the left finger.